1998
DOI: 10.1104/pp.116.4.1431
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Assembly in Diatoms (Bacillariophyceae)1

Abstract: Achnanthes longipes is a marine, biofouling diatom that adheres to surfaces via adhesive polymers extruded during motility or organized into structures called stalks that contain three distinct regions: the pad, shaft, and collar. Four monoclonal antibodies (AL.C1-AL.C4) and antibodies from two uncloned hybridomas (AL.E1 and AL.E2) were raised against the extracellular adhesives of A. longipes. Antibodies were screened against a hot-water-insoluble/ hot-bicarbonate-soluble-fraction.The hot-water-insoluble/hotb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…The major aim of this study was to compare the ovoid and fusiform EPS to ascertain whether a difference in polysaccharide or protein composition could be identified in relation to cell adhesion. Wustman et al (1998) suggested increased Rha and Fuc content could be related to adhesion, as these hydrophobic polymers could increase surface interactions. In this study the constituent monosaccharide profiles and linkages of the fractions that correspond to extracellular mucilage (OM, OB, OF, FF) for the ovoid and fusiform cultures are broadly similar (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The major aim of this study was to compare the ovoid and fusiform EPS to ascertain whether a difference in polysaccharide or protein composition could be identified in relation to cell adhesion. Wustman et al (1998) suggested increased Rha and Fuc content could be related to adhesion, as these hydrophobic polymers could increase surface interactions. In this study the constituent monosaccharide profiles and linkages of the fractions that correspond to extracellular mucilage (OM, OB, OF, FF) for the ovoid and fusiform cultures are broadly similar (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, independent of the deoxysugar origin, these sugars have been reported to have hydrophobic properties. As these properties became more pronounced throughout the incubation period, the carbohydrate pool also became more hydrophobic (Giroldo et al, 2003) and, therefore, more susceptible to aggregation, as the enhancement of the hydrophobic properties of TDCHO increases the tendency for aggregation in the medium (Wustman, Gretz & Hoagland, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The data available on the composition of phytoplanktonic EPS as well as EPS utilization by bacteria are quite rare, considering the number of taxa, and are especially sparse for planktonic freshwater diatoms. Most results concern biofouling organisms (Cooksey and Cooksey 1985, Wustman et al 1997) or epipelic diatoms (Smith and Underwood 1998, Underwood and Smith 1998, Staats et al 1999). The structure and composition of the EPS have remarkable influence on their physical and chemical properties, defining many of the features of such EPS.…”
mentioning
confidence: 99%